A Kaleidoscopic Navigation Through Different Shades of Colors in Dermoscopy - Ankad, Balachandra S; Adya, Keshavmurthy A (Nepal Journal of Dermatology, Venereology & Leprology, 2024)
Dermoscopy has traveled a long way from its initial application limited to tumoral dermatology, especially melanocytic tumors, to its indispensable role in general dermatology as well as in procedural dermatology. Dermoscopy primarily serves as a diagnostic tool by virtue of its ability to visualize skin surfaces and sub-surface structures in a magnified and illuminated manner. Colors are critical and significant in dermoscopy. They are imparted by different chromophores in skin tissue. Hence, recognition of diverse colors and their variations is of paramount importance in the analysis of a dermoscopic image. In this review, we describe the various colors observed in dermoscopy, emphasizing the same in order to interpret them appropriately for an accurate diagnosis.